Comparative study of precise measurements of natural radionuclides and radiation dose using in-situ and laboratory γ-ray spectroscopy techniques - N. M. Hassan (Nature Portfolio, 2018)
Abstract In this study, in-situ and laboratory γ-ray spectroscopy techniques were compared to evaluate the activity concentration of natural radionuclides in soil. The activity concentrations of 238U (226Ra), 232Th, and 40K in the soil in 11 sites were simultaneously measured with in-situ portable HPGe and the NaI(Tl) detectors. In parallel, 55 soil samples collected from these sites were analyzed with a laboratory γ-ray spectroscopy technique (HPGe). A strong correlation was observed between the in-situ and laboratory HPGe techniques with a linear correlation coefficient (R2) of 0.99 for 226Ra and 232Th and 0.975 for 40K, respectively. The in-situ HPGe technique shows a strong correlation with the NaI(Tl) detector. γ-Rays cps of 226Ra, 232Th, and 40K of the NaI (Tl) detector were then converted to specific activities (Bq kg−1 unit) in soil using the empirical formulas obtained in this study. The absorbed dose rate in air at 1 m height above ground due to these radionuclides was calculated using the Beck’s formula and the results were compared with measured values obtained with an high pressure ionization chamber. The results of the calculated and measured dose rate show a strong correlation of R2 = 0.96. The reliability and precision of analytical spectroscopy techniques of radioactivity and radiation dose were confirmed in this work.